5 things to know about FAFSA prior‐prior‐year implementation. Issue 11 (16th December 2015) - Sutton, Halley
Abstract : SAN DIEGO — In a packed session at this year's National Association for College Admission Counseling national conference, three presenters covered the nuts and bolts of the changes in incorporating prior‐prior‐year financial data on the upcoming Free Application for Federal Student Aid. Sarah Summerhill of Michigan State University, Eileen O'Leary of Stonehill College, and Todd Rinehart of the University of Denver introduced the changes, explained what the changes mean for higher education financial aid, gave an overview of possible upcoming changes to the admission process because of the PPY change, and reviewed best practices for implementing potential changes. Here are the top five things officials in the Registrar's Office need to know.